Step
*
1
of Lemma
not-not-Ramsey
1. R : ℕ ⟶ ℕ ⟶ ℙ
2. ∀s:StrictInc. ∃n:ℕ. (¬homogeneous(R;n;s))
3. n : ℕ
4. s : {s:ℕn ⟶ ℕ| strictly-increasing-seq(n;s)} 
5. ¬homogeneous(R;n;s)
6. m : ℕ
7. strictly-increasing-seq(n + 1;s.m@n)
⊢ ¬homogeneous(R;n + 1;s.m@n)
BY
{ (ParallelOp -3 THEN FLemma `homogeneous-extension-implies` [-1] THEN Auto) }
Latex:
Latex:
1.  R  :  \mBbbN{}  {}\mrightarrow{}  \mBbbN{}  {}\mrightarrow{}  \mBbbP{}
2.  \mforall{}s:StrictInc.  \mexists{}n:\mBbbN{}.  (\mneg{}homogeneous(R;n;s))
3.  n  :  \mBbbN{}
4.  s  :  \{s:\mBbbN{}n  {}\mrightarrow{}  \mBbbN{}|  strictly-increasing-seq(n;s)\} 
5.  \mneg{}homogeneous(R;n;s)
6.  m  :  \mBbbN{}
7.  strictly-increasing-seq(n  +  1;s.m@n)
\mvdash{}  \mneg{}homogeneous(R;n  +  1;s.m@n)
By
Latex:
(ParallelOp  -3  THEN  FLemma  `homogeneous-extension-implies`  [-1]  THEN  Auto)
Home
Index